2005
DOI: 10.1086/432911
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Elemental Abundance Ratios in Globular Clusters, Field Stars, and Dwarf Spheroidal Galaxies

Abstract: We have compiled a sample of globular clusters with high-quality stellar abundances from the literature to compare to the chemistries of stars in the Galaxy and in dwarf spheroidal galaxies. Of the 45 globular clusters examined, 29 also have kinematic information. Most of the globular clusters belong to the Galactic halo; however, a significant number have disk kinematics or belong to the bulge. Focusing on the [ /Fe] and light r-process element ratios, we find that most globular cluster stars mimic field star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
368
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(421 citation statements)
references
References 132 publications
48
368
5
Order By: Relevance
“…As expected from chemical evolution studies of the Milky Way (e.g., Matteucci 2001), we know that [α/Fe] decreases with [Fe/H], after a plateau, at [Fe/H] ∼ −1. This trend is also evident in the entire sample of GCs by Pritzl et al (2005).…”
Section: Index-index Diagramssupporting
confidence: 54%
See 1 more Smart Citation
“…As expected from chemical evolution studies of the Milky Way (e.g., Matteucci 2001), we know that [α/Fe] decreases with [Fe/H], after a plateau, at [Fe/H] ∼ −1. This trend is also evident in the entire sample of GCs by Pritzl et al (2005).…”
Section: Index-index Diagramssupporting
confidence: 54%
“…In particular, we use the average -over several works and several stars in each globular cluster -abundances and abundance ratios by Pritzl et al (2005) The aim of the project is to provide an empirical calibration relation to convert Lick indices into abundances for a large range in both and . The correlation between Lick indices such as Fe (or Mgb) and [Fe/H] has already been shown and discussed by other works, the latest and most accurate study being that of Puzia et al (2002), for a very similar range in [Fe/H].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the s-process ratio [Ba/Y] is in full agreement with the halo fields stars within the scatter. However, Pritzl et al (2005) have shown that, in comparison with (thick) disk GCs, the halo clusters tend to be offset more towards higher [Ba/Y] ratios, and so are the dSphs. The latter is usually interpreted in terms of the low star formation efficiencies of the dSph galaxies, which leaves room for a much stronger contribution from metal-poor AGB stars that are the main sites of the s-process (e.g., Busso et al 2001;Lanfranchi et al 2008).…”
Section: Halo Field Starsmentioning
confidence: 99%
“…Here we do not aim for a comprehensive comparison with the entire MWGC population (e.g., Pritzl et al 2005;Geisler et al 2007). Rather, we wish to simply compare Pal 4 to a few clusters that have been selected as broadly representative of the inner and outer halo cluster systems.…”
Section: Halo Globular Clustersmentioning
confidence: 99%
“…This becomes particularly evident when analyzing their respective trends with [Fe/H] (e.g., [86,71] Recently, it has become particularly clear that the Galactic bulge follows a different enrichment law than does the Galactic thick disk, which in turn follows a different law from the thin disk (e.g., [91,23,1,50,31,76]). As pointed out by several of the quoted authors, the overabundance in at least some of the α-capture elements up to high metallicities for the bulge stars likely indicates a very short formation timescale for the Galactic bulge, whose chemical enrichment seems accordingly to have been dominated by ejecta from type II supernova (SN II) explosions.…”
Section: The Helium Enrichment "Law" In Different Stellar Populationsmentioning
confidence: 99%